Promoter methylation of GATA4, WIF1, NTRK1 and other selected tumour suppressor genes in ovarian cancer - Chmelařová, M; Dvořáková, E; Špaček, J; Laco, J; Mžik, M; Palička, V (Folia biologica, 2013)
Ovarian cancer is the leading cause of death from gynaecologic tumours, but the molecular and especially epigenetic events underlying the transformation are poorly understood. Various methylation changes have been identified and show promise as potential cancer biomarkers. The aim of this study was to investigate promoter methylation of selected tumour suppressor genes in ovarian cancer by comparison with normal ovarian tissue. To search for epigenetic events we used methylation-specific multiplex ligation-dependent probe amplification to compare the methylation status of 44 tissue samples of ovarian cancer with 30 control samples. Using a 20% cut-off for methylation, we observed significantly higher methylation in genes NTKR1, GATA4 and WIF1 in the ovarian cancer group compared with the control group. These findings could potentially be used in screening of ovarian cancer, and may have implications for future chemotherapy based on epigenetic changes.
Keywords: dospělí; nádory vaječníků; Female; Repressor Proteins; Adaptor Proteins, Signal Transducing; represorové proteiny; Adult; mladý dospělý; ženské pohlaví; nádorové supresorové proteiny; adaptorové proteiny signální transdukční; receptor trkA; lidé; Ovarian Neoplasms; GATA4 Transcription Factor; studie případů a kontrol; Aged, 80 and over; Receptor, trkA; metylace DNA; Tumor Suppressor Proteins; Case-Control Studies; Aged; Young Adult; DNA Methylation; lidé středního věku; senioři nad 80 let; senioři; promotorové oblasti (genetika); Promoter Regions, Genetic; Middle Aged; transkripční faktor GATA4; Humans